Streptococcus agalactiae Infection in Wild Trahira (Hoplias malabaricus) and Farmed Arapaima (Arapaima gigas) in Brazil: An Interspecies Transmission in Aquatic Environments Shared with Nile Tilapia (Oreochromis niloticus) - Carlos Augusto Gomes Leal; Rafael Gariglio Clark Xavier; Guilherme Alves de Queiroz; Tarcísio Martins França Silva; Júnia Pacheco Teixeira; Flávia Figueira Aburjaile; Guilherme Campos Tavares (Microorganisms)
Streptococcus agalactiae is an important pathogen responsible for cases of high mortality in farmed and wild fish worldwide. In Brazil, this bacterium has been commonly associated with outbreaks in Nile tilapia farms, but other native fish species are also susceptible. Since floating cages are one of the most common culture systems used in the country, the close contact between farmed tilapia and native fish species presents a risk concerning the transmission of this pathogen. In this study, we characterized a mortality outbreak in free-living trahira and in farmed arapaima, as well as the genetic and antimicrobial susceptibility patterns of the isolates obtained. During the outbreaks, moribund fish were sampled and subjected to bacterial examination, after which the isolates were identified via MALDI-ToF analysis. Genotyping was evaluated using repetitive sequence-based PCR (REP-PCR) and multilocus sequence typing (MLST). Antimicrobial susceptibility was evaluated using disc diffusion assays. In addition, whole-genome analysis also was performed. S. agalactiae was identified in all diseased fish, all of which belonged to serotype Ib; however, trahira strains were classified as non-typeable lineages in the MLST assay, while arapaima strains were classified as ST260. These isolates were shown to be similar to the main genotype found in Nile tilapia in Brazil, using REP-PCR, MLST and phylogenomic analysis. The pathogenicity of the bacterium was confirmed by Koch’s postulates for both fish species. The antimicrobial susceptibility assay showed variable results to the same antibiotics among the isolates, prompting four of the isolates to be classified as multidrug-resistant. This study represents the first report of a natural outbreak of Streptococcus agalactiae infection in wild trahira and farmed arapaima inhabiting the same aquatic environment as Nile tilapia.